2020
DOI: 10.1007/s00392-020-01614-z
|View full text |Cite
|
Sign up to set email alerts
|

Compared with matched controls, patients with postoperative atrial fibrillation (POAF) have increased long-term AF after CABG, and POAF is further associated with increased ischemic stroke, heart failure and mortality even after adjustment for AF

Abstract: Objective To analyze (1) associations between postoperative atrial fibrillation (POAF) after CABG and long-term cardiovascular outcome, (2) whether associations were influenced by AF during follow-up, and (3) if morbidities associated with POAF contribute to mortality. Methods An observational cohort study of 7145 in-hospital survivors after isolated CABG (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), with preoperative sinus rhythm and without AF history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 40 publications
(90 reference statements)
7
39
1
1
Order By: Relevance
“…Postoperative atrial fibrillation is a secondary AF, but it should be considered as an independent entity. Previous studies have shown that patients with POAF have taken a 3- to 8-time risk of developing future AF and have higher risks of cerebrovascular events and cardiovascular mortality ( 10 , 11 ). However a cohort study demonstrated that AF developing late after operation, rather than POAF, is independently associated with long-term mortality ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative atrial fibrillation is a secondary AF, but it should be considered as an independent entity. Previous studies have shown that patients with POAF have taken a 3- to 8-time risk of developing future AF and have higher risks of cerebrovascular events and cardiovascular mortality ( 10 , 11 ). However a cohort study demonstrated that AF developing late after operation, rather than POAF, is independently associated with long-term mortality ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have shown that new-onset POAF following CABG was associated with a significantly higher risk of short and long-term mortality, the long-term stroke risk remained controversial ( 5 , 6 ). Some reported no association ( 7 , 8 ), while some advocated increased risk of stroke after cardiac surgery ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…After a median follow-up of more than 6 years, patients with POAF had a higher probability of recurrent AF (25.4% vs 3.6%; adjusted OR, 8.31; 95% CI, 4.20-16.43; P < 0.001), a higher probability of late all-cause mortality (29.7% vs 14.8%; adjusted HR, 1.57; 95% CI, 1.05-2.34; P ¼ 0.027), and a higher probability of death from cerebral ischemia (4.2% vs 0.2%; P < 0.001) compared with patients without POAF. A very recent analysis 807 took this observational comparison further with a larger sample size, prospectively collected data, longer follow-up, and a matched cohort evaluation. This report considered 7145 consecutive Values and preferences.…”
Section: Prognosis Of Postoperative Atrial Tachyarrhythmiasmentioning
confidence: 99%
“…While most observational studies have shown an association between POAF and short-term stroke risk, [9][10][11] conflicting results among published studies have raised uncertainty on whether the association persists during long-term follow-up. 3,[12][13][14] Defining the exact magnitude of the excess stroke risk in patients with POAF would be crucial in order to determine whether anticoagulation may have a meaningful effect that outweighs the risks of bleeding. To address these issues, we performed a 5/32 systematic review and meta-analysis evaluating the short-term and long-term relative and absolute risks of stroke in patients with POAF after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%